Optimization of fermentative parameters to improve Gamma- Aminobutyric Acid (GABA) production by Lactiplantibacillus plantarum B13 - Tan, Shang Wei; Koh, Yao Zu; Siva, Sangkaran; Wasoh, Helmi; Mohamed, Mohd Shamzi; Sobri, Zulfazli M; Halim, Murni (Hibiscus Publisher Enterprise, 2024)
Gamma-aminobutyric acid (GABA) is a major inhibitory neurotransmitter in the mammalian brain, and it possesses several physiological properties, such as depression reduction and anxiety release. GABA production by microbial synthesis is favoured over other methods like enzymatic and chemical synthesis due to the ease of operation and less formation of harmful pollutants. Lactic acid bacteria are widely applied for GABA production because of high GABA yield and their Generally Recognized as Safe (GRAS) status , which is critical in food and ingredient safety. In this study, various fermentation conditions, including incubation time, pH, temperature, monosodium glutamate (MSG) concentration, pyridoxal-5’-phosphate (PLP) concentration and glucose concentration were screened by one-factor-at-a-time strategy to achieve the optimal GABA production by a potential probiotic strain, Lactiplantibacillus plantarum B13. The result revealed the strain exhibited the optimal GABA production of 19.073 ± 0.5214 g/L with the highest GABA productivity of 0.424 g/L/h under fixed conditions: incubation time of 66 hours, pH 5.5, temperature of 35°C, MSG concentration of 5% (w/v), PLP concentration of 0.7 mM PLP and glucose concentration of 60 g/L. The findings of this study show that fermentation parameters are dependent on species and strains due to the different properties of glutamic acid decarboxylase enzymes and optimization of single parameters is important as a preliminary step to identify the range of fermentation factors that affect GABA yield prior further research endeavours. This study also has great implications for GABA production by L. plantarum B13 and provides a prerequisite for developing new healthy products enriched with GABA as daily supplements to support relaxation and regulate mood, reduce stress and promote better sleep.